Balochistan Province, Pakistan : Procurement Systems Performance Assessment - World Bank (Washington, DC, 2012)
Balochistan is the largest province in Pakistan, with 44 percent (347,000 sq. kms.) of the land area but only 5 percent of the population (6.5 million). The province is blessed with a large number of natural resources which are to a great extent unexplored and unutilized. It has an 1100-kilometer coastline which can prove to be an important trade corridor in the region by connecting China and Central Asian republics in the north to the sea in the south and India, Bangladesh in the East. Economic development is needed to deal with significant structural problems both political and socio-economic. Under the auspices of The World Bank, this intervention for assessing the procurement systems of the provincial with the objective of benchmarking the performance of procurement management systems was embarked upon. This report covers the assessment for the province of Balochistan undertaken in the month of September 2006. This snapshot of procurement systems performance assessment is mainly based on historical data and current practices observed during the mission.